Assessing efficiency in public service obligations in European air transport using data envelopment analysis - Costa, J. (2021)
In recent years, the use of Public Service Obligations (PSOs) in air transport policy has substantially increased. In remote regions, where air transport services are not profitable, the application of this subsidy program is crucial for the economic and social development of these regions. However, there is a great diversity in the provision of PSO services among different regions in Europe. Therefore, it is essential to assess the performances of the air carriers operating in different PSO routes. The present study uses Data Envelopment Analysis (DEA) to assess the efficiency of PSO routes within the European Union and compares them with the performances of the operating airlines, both when operating under this subsidy program and when operating their regular flights. First, DEA was applied to the annual data of several European airlines, and then applied to the data of their PSO routes, so that a comparison can be made between the performance obtained on regular flights and flights under the PSO regime. The results identify which airlines had the best and worst performances, as well as the routes and respective regions of Europe where the airlines tend to score higher and lower in terms of efficiency. Results suggest that the Nordic European countries and the United Kingdom were the regions where air carriers obtained the lowest results, and thus, this empirical evidence should support the public authorities to consider revisiting their PSO contracts, in order to improve their operation.